Towards a Value-Based Teacher Professional Digital Competence Framework in Muhammadiyah Education: A Systematic Literature Review - Endah Nur Latifah; Zurqoni Zurqoni; Moh. Mahrus (UIN Sunan Gunung Djati Bandung, 2026)
The rapid advancement of digital technology has transformed educational practices and increased demands for teachers' digital competence. However, within Muhammadiyah educational institutions, digital competence is not only linked to technological and pedagogical capabilities but is also shaped by the organization's principles. This systematic literature review aims to examine the digital competence discussed in studies on Muhammadiyah teachers, explore how these competences are integrated with Muhammadiyah principles, and identify challenges and opportunities in developing values-based digital competence. Using the PRISMA framework, this study reviewed seven eligible articles published between 2022 and 2025 from Scopus, ERIC, DOAJ, and Garuda. The findings indicate that Muhammadiyah teachers' digital competence encompasses both technological and pedagogical competence. Besides, the reviewed studies demonstrate that digital competence is closely linked to the Muhammadiyah principles, particularly Progressive Islam, tadjid, and Manhaj Tarjih, which provide normative guidance for integrating technology into educational settings. In addition, we find several challenges, including limited infrastructure, teacher preparedness, and the scarcity of Islamic values-based digital resources, while highlighting opportunities through professional development, institutional support, collaboration, and digital innovation. Based on a synthesis of the reviewed studies, this study proposes a Muhammadiyah Teacher Professional Digital Competence (TPDC) model consisting of four interrelated dimensions: pedagogical competence, technological competence, Muhammadiyah principles, and development strategies. The proposed model expands the existing TPDC framework by demonstrating that teacher digital competence in Muhammadiyah education is not merely a professional capability but also a value-oriented construct shaped by organizational and religious foundations. Therefore, it contributes to the growing literature on teacher digital competence and provides a conceptual foundation for future empirical research on value-based digital competence in the context of Islamic education.